Proceedings of SPE Production Operations Symposium 2005
DOI: 10.2523/94300-ms
|View full text |Cite
|
Sign up to set email alerts
|

Contact Pressure Threshold: An Important New Aspect of Casing Wear

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The first analytical solution for residual burst strength of worn casing was developed by Song et al 5 Full size tests were conducted and the comparison between actual rupture pressures and predicted values of worn casing verified the accuracy of the method. Hall and Malloy 6 acquired best fitting empirical function for the majority of more than 450 wear tests data and confirmed the nonlinear relationship between casing wear volume and dissipation energy. Sun et al 7 classed wear stages into steady-state wear and running-in wear, and a nonlinear wear prediction model was developed.…”
Section: Introductionsupporting
confidence: 52%
“…The first analytical solution for residual burst strength of worn casing was developed by Song et al 5 Full size tests were conducted and the comparison between actual rupture pressures and predicted values of worn casing verified the accuracy of the method. Hall and Malloy 6 acquired best fitting empirical function for the majority of more than 450 wear tests data and confirmed the nonlinear relationship between casing wear volume and dissipation energy. Sun et al 7 classed wear stages into steady-state wear and running-in wear, and a nonlinear wear prediction model was developed.…”
Section: Introductionsupporting
confidence: 52%
“…Disregarding it can provoke a lot of costs and abandon the well before it reaches the target or, in other special cases to blowout, wear occurs with increasing drilling depth, drilling time, and contact load. [1][2][3][4][5] Bradley and Fontenot determined wear in rotating, tripping, and wireline operations by investigating the effect of time, rotation speed, mud conditions, pipe wear capability, wear resistance, dogleg severity, and tension at the wear point. Moreover, they studied the factors affecting casing wear in these operations and showed that the least wear happens within the wireline and tripping operations.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that the casing wear coefficient is not constant and decreases with increasing wear groove depth. [5] Gao et al investigated the effect of drill pipe diameter on casing wear in ERD wells. They concluded that the casing wears groove geometry is having a substantial impact on the wear groove depth.…”
Section: Introductionmentioning
confidence: 99%